Gluten quality of bread wheat is associated with activity of RabD GTPases. Issue 2 (22nd July 2014) - Tyler, Adam M.; Bhandari, Dhan G.; Poole, Mervin; Napier, Johnathan A.; Jones, Huw D.; Lu, Chungui; Lycett, Grantley W.
Summary In the developing endosperm of bread wheat (Triticum aestivum), seed storage proteins are produced on the rough endoplasmic reticulum (ER) and transported to protein bodies, specialized vacuoles for the storage of protein. The functionally important gluten proteins of wheat are transported by two distinct routes to the protein bodies where they are stored: vesicles that bud directly off the ER and transport through the Golgi. However, little is known about the processing of glutenin and gliadin proteins during these steps or the possible impact on their properties. In plants, the RabD GTPases mediate ER‐to‐Golgi vesicle transport. Available sequence information for Rab GTPases in Arabidopsis, rice, Brachypodium and bread wheat was compiled and compared to identify wheat RabD orthologs. Partial genetic sequences were assembled using the first draft of the Chinese Spring wheat genome. A suitable candidate gene from the RabD clade (TaRabD2a) was chosen for down‐regulation by RNA interference (RNAi), and an RNAi construct was used to transform wheat plants. All four available RabD genes were shown by qRT‐PCR to be down‐regulated in the transgenic developing endosperm. The transgenic grain was found to produce flour with significantly altered processing properties when measured by farinograph and extensograph. SE‐HPLC found that a smaller proportion of HMW‐GS and large proportion of LMW‐GS are incorporated into the glutenin macropolymer in the transgenic dough. Lower protein content but a similar protein profile on SDS‐PAGE was seen in the transgenic grain.